The Role of Interleukin-18 in Barrett's Disease and progression to Oesophageal Adenocarcinoma. - Agnew, Aidan (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
Oesophageal adenocarcinoma (OAC) is characterised as a dismal cancer, with a 5-year survival rate in western countries of less than 20%. The disease is an inflammation-associated cancer, which can begin as a pre-neoplastic inflammatory condition known as Barrett’s oesophagus (or Barrett’s metaplasia), progress into neoplastic dysplasia (pre-malignant cancerous growth of epithelial cells), and then subsequently to an adenocarcinoma, potentially metastasising further. The precursor condition, Barrett’s oesophagus, is increasing in incidence, and is strongly associated with gastro-oesophageal reflux disease (GERD). Metaplasia is defined as the replacement of a fully differentiated cell type with another differentiated cell type. Barrett’s metaplasia occurs at the squamo-columnar junction (SCJ) between the oesophagus and the stomach, due to chronic inflammation in the lower oesophagus. The metaplastic cells that appear at the SCJ during Barrett’s oesophagus have an intestinal phenotype, consisting of terminally differentiated mucus-producing goblet cells, which serve as a histological marker for the diagnosis of this condition. Dysplastic cells grow uncontrollably, amounting to irregular crypt sizes and shapes, where there were previously regular mucus-producing glands composed of terminal goblet cells. Sometimes these areas of dysplasia progress to an adenocarcinoma. Caspase-1 is an inflammatory caspase which mediates the maturation and release of inflammatory cytokines, IL-1β and IL-18, and initiates the inflammatory form of cell death, pyroptosis, in response to canonical inflammasome activation. A previous study carried out by our research group characterised the expression of caspase-1 at different stages of oesophageal disease progression. The study showed that caspase-1 was significantly upregulated in Barrett’s tissue, mediating the release of pro-inflammatory cytokines, and contributing to chronic inflammation, which may act as a mechanism to exacerbate disease. Despite high caspase-1 expression, IL-18 secretion was found to be significantly lower from Barrett’s tissue compared to squamous epithelial tissue. IL-18 has been shown to play anti-tumorigenic roles in the intestine through its immune control over the microbiome distribution and its role in modulating epithelial homeostasis. Given that Barrett’s cells display intestinal phenotypes, it was hypothesised that IL-18 may be functionally capable of exerting a protective, anti-tumorigenic effect on the progression of this disease. This study has gathered evidence to confirm that reduced IL-18 expression occurs during early disease progression, showing that secreted IL-18 levels are significantly lower from Barrett’s compared to adjacent normal tissue, though IL-18 secretion increases again from OAC tissue. Secretion of other pro-inflammatory cytokines like IL-1β, IL-12 and IFN- show a stepwise increase from normal squamous, to Barrett’s, to OAC tissue. IL-18 expression levels were also shown to significantly decrease along disease progression using a human cell line model of disease progression, and a murine model of Barrett’s metaplasia progression. These results collectively suggest that IL-18 may alleviate early metaplastic/dysplastic progression, potentially independently of its pro- inflammatory signalling role, given that opposite trends are seen in expression levels of IL-12 and IFN-. This study presents evidence to suggest that stimulation with recombinant IL-18 may exert a direct signalling role on high-grade oesophageal dysplastic cells in vitro in the form of ERK1/2 activation, which occurred concurrently with increased wound healing. This is suggestive of a potential pro-tumour effect of the cytokine during neoplastic progression. Lastly, this study demonstrated that oesophageal cell lines derived from high-grade dysplastic tissue and adenocarcinoma tissue secrete high levels of IL-18BP, an endogenous IL-18 inhibitor, whereas normal squamous or Barrett’s cell do not. Using bioinformatic analysis of RNAseq data from OAC patients it was observed that high IL-18BP expression in tumours correlated strongly with immune checkpoint (IC) expression. This correlation was further demonstrated in vitro whereby conditioned media from OAC cells stimulated with IFN- (expressing IL- 18BP) caused upregulated TIM-3 and TIGIT expression in NK cells. This suggests that OAC cells secrete IL-18BP and other factors to upregulate immunosuppressive mediators in the tumour microenvironment (TME).
APPROVED
Keywords: Interleukin-18; Inflammasome; Oesophageal adenocarcinoma; Barrett's oesophagus